The Effect of Sediment Supply from Land on Changes in Bathymetry in the Waters of the Rupat Strait, Dumai City, Riau Province - Widuri, Falsabila; Mubarak, Mubarak; Rifardi, Rifardi (Jurnal Perikanan dan Kelautan, 2021)
This research was conducted in February 2021 at the mouth of the Dumai River, Rupat Strait. The purpose of this study was to determine the effect of sediment supply from land on changes in bathymetry in the waters of the Rupat Strait based on the analysis of suspended sediment (SSC) and suspended solids (TSS) divided by the area of the study. The method used is a survey method. The results showed that as much as 26,94 tons/year of sediment entered the Rupat Strait and was distributed in the research area. Each part of the research area has a different bathymetric change value. This is presumably due to oceanographic factors in the waters of the Rupat Strait such as strong and weak river currents when entering the sea, the distance between the research area and the sediment supply source, human activities in each part of the study area, erosion along the river and abrasion at the river mouth. the presence of mangrove forests, dominant sediment types, sloping water topography, the cross-sectional width of the river as a sediment supplier, and suspended solids.